MHD natural convection of a CNT-based nanofluid-filled annular circular enclosure with inner heat-generating solid cylinder - Tayebi, Tahar; Öztop, Hakan Fehmi; Chamkha, Ali J. (Springer Heidelberg, 2021)
The present work is dedicated to understanding the natural convective flow mechanism and heat exchange under magnetic field within a concentric circular annulus between a heat-generating conductive internal cylinder and an isothermally cold external cylinder filled with a CNTs-water-based nanoliquid. The free convective flow is generated by the temperature gradient created between the inner heat-generating solid cylinder and the outer cold cylinder. The flow equations in their dimensionless form are numerically solved via the technique of finite volume. The dependency of various factors and their interrelationships affecting the thermo-hydrodynamic behavior and heat exchange rate within the system has been delineated. The findings of this study emphasize the role of the considered control parameters with regards to the hydro-thermal characteristics and the heat exchange rate within the annulus.
Keywords: Horizontal Cylindrical Annulus; Confocal Elliptic Cylinders; Eccentric Annulus; Al2O3-Water Nanofluid; Water Nanofluid; Magnetic-Field; Porous-Medium; Wavy Cavity; Flow; Enhancement